SPORT EVENTS AS A COMPONENT OF TOURIST DESTINATION DEVELOPMENT STRATEGIES (BASED ON THE EXAMPLE OF THE SNOWBOARD WORLD CUP, BANSKO 2025) (TRAKIA JOURNAL OF SCIENCES, 2025)
Travel industry plays a pivotal role in the recent socio-economic relations, by encouraging economic growth, cultural exchange and technological innovation. Sports provide a huge potential for the implementation of innovative product policy in tourism.The main objective of this survey is to explore and analyse the role of sport events within the tourism destination development strategies.The research tasks are:Targeted research and analysis of the sports’ role as an essential component of the development of the travel industry in Bulgaria.Implementation of a situational (SWOT analysis) based on experts’ judgement, related to the role of sport event in the development of the tourist destination.Conducting a structured interview with experts in the organization and hosting of the event.The following research methods were used: content analysis, SWOT analysis, structured interview.During the research, the following improvement opportunities offered by the event to the tourist destination were identified: tourist infrastructure expansion and upgrade, brand new tourist packages and services design, including sport activities, stimulation of local businesses and entrepreneurship and expansion of the scope of these activities, destination growth and recognition in the context of sustainable tourism.